(3GdGHJgGL TQM GdefgGL aj aQhY GdTGaYjIs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3Gdfhhj , jMji Hf TQa Hf eQj Hf MSf, CHh RcQjG eMjj GdOjf,J (B676 (3g` s ((3YHOGdYRjR Hf eMeO GHf eXaQ GdHdbjfj GdcfGfj GdTGaYj s)
(3ChdgG (B:s
(3jHJOF HChd cJGH GdCbQGQ s
(3BNQgG (B:s
(3BNQ HGH EMjGA GdehGJ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1873s
Keywords: (3GdMOjK h GdeUWdMs